2018
DOI: 10.23851/mjs.v28i3.551
|View full text |Cite
|
Sign up to set email alerts
|

Study the Effect of Interleukin36 Gamma and AMH in Iraqi Women with PCOS

Abstract: Polycystic ovary syndrome (PCOS) is one of the most common female endocrine disorders and affect approximately (5-10) % of women of reproductive age. Anti-Müllerian hormone (AMH) is a homodimeric glycoprotein, a member of the transforming growth factor-β superfamily, it is secreted exclusively from women by granulose cells of ovarian follicles and it is considered as the precise marker of follicle pool size. AMH has been shown to be a good surrogate marker for polycystic ovary syndrome (PCOS). Interleukins are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…These differences can be reported due to different study backgrounds in terms of varied weather conditions, diverse study population and risk factors like having pets, domestic animals, unhealthy hygienic practice, and eating pattrens (Zemene et al, 2012;Agmas et al, 2015;Abamecha and Awel 2016;Bamba et al, 2017;Frimpong et al, 2017). The study showed significant relation between Toxoplasma gondii and the host suffering from hepatitis, diabetes, nausea, and arthritis which agrees with statement toxoplasmosis affects liver and kidney functions due to increase in the levels of some biochemical parameters in patients group; exhibit severe medical conditions such as pneumonia, hepatitis, blindness and severe brain abnormalities (Al-Fartusie et al, 2012).…”
Section: Host Disease Wise Prevalencesupporting
confidence: 64%
“…These differences can be reported due to different study backgrounds in terms of varied weather conditions, diverse study population and risk factors like having pets, domestic animals, unhealthy hygienic practice, and eating pattrens (Zemene et al, 2012;Agmas et al, 2015;Abamecha and Awel 2016;Bamba et al, 2017;Frimpong et al, 2017). The study showed significant relation between Toxoplasma gondii and the host suffering from hepatitis, diabetes, nausea, and arthritis which agrees with statement toxoplasmosis affects liver and kidney functions due to increase in the levels of some biochemical parameters in patients group; exhibit severe medical conditions such as pneumonia, hepatitis, blindness and severe brain abnormalities (Al-Fartusie et al, 2012).…”
Section: Host Disease Wise Prevalencesupporting
confidence: 64%
“…The study revealed that 32 (30.47 %) of patients were at the age group of (20-25) years, that 26 (24.76 %) of patients were at the age group of (31-35) years, that 19 (18.09 %) of patients were at the age group of (26-30) years, that 15 (14.28 %) of patients were at the age group of (36-40) years and than that 13 (12.38 %) of patients were at the age group of (41-45) years as shown in table [1]. This result is in agreement with [14] and not agreement with [15], [16] and [17]. The similarities between these studies regarding the same age group because PCOS appeared at menarche and the women became symptomatic later but most women with PCOS are diagnosed when their age between 20-30 years [18].…”
Section: Clinical Studymentioning
confidence: 66%
“…The increase of production of AMH prompt the decrease in the sensitivity of follicles to FSH at levels of receptors,which is very necessary for growing of this follicles,it leads to an increase of the numbers of antral follicles on the detriment of their size and the number of small antral follicles size(2-5mm)increases, therefore failure the selection of the dominant follicle and anovulation occur with oligo or amenorrhea (22) .…”
Section: Resultsmentioning
confidence: 99%